2016
DOI: 10.1002/anie.201601402
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of the Catalytic Activity of a Metal Hydride in CO2 Reduction

Abstract: Atomic hydrogen on the surface of a metal with high hydrogen solubility is of particular interest for the hydrogenation of carbon dioxide. In a mixture of hydrogen and carbon dioxide, methane was markedly formed on the metal hydride ZrCoHx in the course of the hydrogen desorption and not on the pristine intermetallic. The surface analysis was performed by means of time-of-flight secondary ion mass spectroscopy and near-ambient pressure X-ray photoelectron spectroscopy, for the in situ analysis. The aim was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 29 publications
(3 reference statements)
0
30
0
Order By: Relevance
“…Figure 8 shows the results of catalytic testing and sample weight and surface areas are presented in exhibited much lower reactivity than Mg 2 Ni, as shown in Figure 8. Therefore, the formation of the hydride phase, Mg 2 NiH 4 , reduced catalytic activity in the hydrogenation of C 2 H 2 , in contrast to CeNi 5-x Ga x alloys and previous reports [4,23,24,26,29,[31][32][33][34]36]. After annealing, the Mg 2 NiH 4 disappeared and Mg 2…”
Section: Catalytic Tests Of Ceni 5-x Ga X (X = 0 125 15) Alloysmentioning
confidence: 77%
See 1 more Smart Citation
“…Figure 8 shows the results of catalytic testing and sample weight and surface areas are presented in exhibited much lower reactivity than Mg 2 Ni, as shown in Figure 8. Therefore, the formation of the hydride phase, Mg 2 NiH 4 , reduced catalytic activity in the hydrogenation of C 2 H 2 , in contrast to CeNi 5-x Ga x alloys and previous reports [4,23,24,26,29,[31][32][33][34]36]. After annealing, the Mg 2 NiH 4 disappeared and Mg 2…”
Section: Catalytic Tests Of Ceni 5-x Ga X (X = 0 125 15) Alloysmentioning
confidence: 77%
“…A number of studies have reported that absorbed hydrogen is essential for hydrocarbon hydrogenation, with Pd containing absorbed hydrogen showing high reactivity [24][25][26][27][28][29][30][31]. Since the state of absorbed hydrogen is similar to a dissociative hydrogen atom, hydrogen storage alloys have been used as catalysts for hydrogenation of C 2 H 4 and CO 2 [32][33][34][35][36]. Using a hydrogen storage alloy as a catalyst is a new approach to catalysis, however, few studies about hydrogen storage alloys and the selectivity of products from catalysis for hydrogenation of alkynes have been reported [4].…”
Section: Introductionmentioning
confidence: 99%
“…The same is true for another reaction that was tested, namely the formation of methane during the hydrogenation of CO 2 using a ZrCoH x catalyst [163]. Cobalt is probably in a reduced state, but the availability of hydrogen from the metal hydride was essential to observe methane production.…”
Section: Using Metal Hydrides As Catalystsmentioning
confidence: 73%
“…Borohydrides can also be potentially used as catalysts to facilitate the hydrogen uptake and release during chemical reactions, such as the hydrogenation of CO2, as demonstrated by many metal hydrides. [148,149]…”
Section: Resultsmentioning
confidence: 99%